IMPACT OF DIABETES MELLITUS ON SURVIVAL RATES AFTER HEART TRANSPLANTATION - Bedanova, Helena; Ondrasek, Jiri; Cerny, Jan; Orban, Marek; Spinarova, Lenka; Hude, Petr; Krejci, Jan; Nemec, Petr (Biomedical papers, 2009)
Aims: Heart transplantation (HTx) is the most effective therapy in patients with end-stage heart failure. Diabetesrelated complications are relative contraindications for heart transplantation. The aim of our study was to analyse the impact of DM (diabetes mellitus) at the time of heart transplantation and new-onset post-transplantation DM on long-term survival.Methods: A retrospective database analysis was performed on all patients who had undergone HTx at our institution between 4/1997 and 9/2007. Patients were divided into three groups: Group A - patients without DM; Group B - patients with new onset of DM after HTx; Group C - patients with DM prior to HTx.Results: Patients with DM before the surgery were more obese, their BMI was 27.7 ± 2.90, compared to groups A and B with BMI of 24.7 ± 3.37 and 25.3 ± 3.64 respectively (p = 0.0003). Patients in group B had statistically significantly higher risk of developing acute rejection (G 1B and more according to International Society of Heart and Lung Transplantation - ISHLT - classification) (p = 0.0350). The incidence of infections between individual groups showed no statistically significant differences (p = 0.5839). Five-year survival in group A was 82%, 10-year survival was 73%. Corresponding numbers for group B were 86% and 78%, for group C 86% and 83%. Differences between groups were not statistically significant (p = 0.2560).Conclusions: DM in patients after heart transplantation in our study had no effect on long-term survival of patients. Post-transplantation DM increases risk of acute rejections. Pre-transplantation DM was associated with excessive bodyweight or obesity.
Keywords: Heart transplantation/Diabetes mellitus/Survival analysis